Inter-temporal changes in ethnic urban earnings disparities in China - Sai Ding; Shi Li; Samuel L. Myers (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2011)
Chapter from: 'Rising Inequality in China: Challenge to a Harmonious Society', edited by Shi Li, Hiroshi Sato and Terry Sicular.
Keywords: 330; Einkommen; Ethnische Gruppe; Einkommensverteilung; Disparitätsmaß; Ballungsraum; China